El Jengibre como recurso potencial en la prevención y/o tratamiento para Covid-19 en el distrito de Breña – Lima - Tarazona Lévano, Juan Carlos; Turco Condori, Thalía Gabriela (Universidad Privada de Huancayo Franklin Roosevelt, 2022)
Tiene por objetivo. Determinar el grado de cognición sobre la utilización del Jengibre para prevención y/o procedimiento del SARS–CoV-2 en el distrito de Breña – Lima. Frente a la situación difícil que venimos atravesando resulta de vital importancia tener conocimiento acerca de los tratamientos alternativos y complementarios para poder reforzar el sistema inmunológico. Metodología. Modelo de indagación, prospectivo, transversal y observacional; diseño no experimental. – descriptivo. Se Concluyó que El nivel de conocimientos de la población del distrito de Breña acerca del uso de Jengibre cono tratamiento y/o prevención del Covid-19, es de nivel medio

Its objective is. To determine the degree of cognition about the use of Ginger for prevention and/or procedure of SARS-CoV-2 in the district of Breña - Lima. Given the difficult situation we are going through, it is of vital importance to have knowledge about alternative and complementary treatments to strengthen the immune system. Methodology. Prospective, cross-sectional and observational model of inquiry; non-experimental design. - Descriptive. It was concluded that the level of knowledge of the population of the district of Breña about the use of ginger as a treatment and/or prevention of Covid-19 is medium
Ginger as a potential resource in the prevention and/or treatment for Covid - 19 in the district of Breña – Lima
Keywords: Jengibre; Propiedades farmacológicas; Covid-19; http://purl.org/pe-repo/ocde/ford#3.01.05